Size dependence of Au NP-enhanced surface plasmon resonance based on differential phase measurement - Zeng, Shuwen (2014)
The impact of spherical gold nanoparticles (Au NPs) with diameters of 40–80 nm for the enhancement of surface plasmon resonance (SPR) sensing signals is presented. Numerical analysis is given to simulate the perturbation of evanescent field in the presence of Au NPs. The results indicate that Au NPs with 40 nm possess the highest coupling effect when the separation of Au NP and SPR sensing film is fixed at 5 nm. For experimental demonstrations, colloidal Au NPs with different sizes but unified extinction coefficient (optical density) are immobilized onto SPR sensing films respectively through a spacer, dithiothreitol (DTT). Phase changes of the reflected SPR signals, which are associated with the plasmonic coupling between the NPs and sensing film, are monitored using a differential phase SPR sensor. Results obtained from the experiments show good agreement with the theoretical studies. This work can considerably serve as a solid guidance for future development of Au NPs-enhanced SPR sensors.